STRATEGI PEMASARAN PENDIDIKAN DALAM MENGATASI PENURUNAN JUMLAH SISWA DI SDN 06 LASI MUDO KECAMATAN CANDUANG - Yakub Simbolon, Ali Mustopa; Junaidi, Junaidi; Sumarni, Weni; Sermal, Sermal; Bashori, Bashori (UIN Imam Bonjol Padang, 2024)
This research focuses on SDN 06 Lasi Mudo, which has experienced a decline in new student enrollments. The conflict involves human factors, particularly human resource management, encompassing teachers, administrative staff, and students, withthe school principal as the key leader.The research method employs a case study approach, analyzing human resource conflict, marketing strategies, improvement of educator quality, and infrastructure management at the school. Data were collected through interviews, observations, and documentation, with the research subjects involving SDN 06 Lasi Mudo. The research results indicate that marketing strategies, improvement of educator quality, and physical resource management can be solutions to address the conflict and the decline in new student enrollments.The effective implementation of conflict management is crucial inresponding to differences in the school environment.This research provides a significant contribution to understanding the complexity of factors influencing the decrease in the number of new students in elementary schools.The implications include the development of more effective policies and strategies to enhance the quality of education at the elementary level. The success of SDN 06 Lasi Mudo demonstrates that the quality of education depends not only on physical facilities but also on human resource management and wise strategies.